2023
DOI: 10.17582/journal.aavs/2023/11.6.864.869
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Molecular Detection of Cryptosporidium Parasite in Quails (Coturnix coturnix) in Baghdad Province, Iraq

Abstract: A mong the most common enteric protozoan parasite that affects a variety of host animals is Cryptosporidium. Many Cryptosporidium spp. that have been linked to zoonotic illnesses across the globe include C. andersoni C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…These findings align with the morphological descriptions reported in previous research (24,25). Furthermore, the application of the PCR technique, as documented in a preceding study (26), confirmed the identity of the detected parasite as C. meleagridis.…”
Section: Morphological Characterizationsupporting
confidence: 92%
“…These findings align with the morphological descriptions reported in previous research (24,25). Furthermore, the application of the PCR technique, as documented in a preceding study (26), confirmed the identity of the detected parasite as C. meleagridis.…”
Section: Morphological Characterizationsupporting
confidence: 92%